Investigation and Research on the High-quality Development of Night Tourism Scene in Qixingyan Scenic Area of Zhaoqing - Chen, Haiming; Wen, Rou (International Journal of Social Sciences and Public Administration, 2025)
As a vital extension of urban tourism, Qixingyan Scenic Area’s nighttime tourism faces challenges including limited product diversity, insufficient cultural integration, and underdeveloped supporting services. This study systematically analyzes the current state of nighttime tourism in the scenic area. Through questionnaire surveys and tourist interviews, it reveals that visitors are predominantly young people from within the province, with low satisfaction regarding supporting facilities. Based on these findings, the study proposes innovative approaches such as developing diversified product systems, enhancing cultural transformation, optimizing transportation and catering services, and strengthening government coordination. Specific recommendations include leveraging new media marketing to attract out-of-province visitors, fostering talent through school-enterprise collaboration, and establishing dynamic feedback mechanisms. The conclusions provide data-driven support and practical references for the high-quality development of nighttime tourism in Qixingyan Scenic Area and similar attractions.